Lecture 13. The Carnot Cycle. - Penner, Reginald (University of California Irvine (UCI), 2012)
UCI Chem 131C Thermodynamics and Chemical Dynamics (Spring 2012)
Lec 13. Thermodynamics and Chemical Dynamics -- The Carnot Cycle --

Instructor: Reginald Penner, Ph.D.

Description: In Chemistry 131C, students will study how to calculate macroscopic chemical properties of systems. This course will build on the microscopic understanding (Chemical Physics) to reinforce and expand your understanding of the basic thermo-chemistry concepts from General Chemistry (Physical Chemistry.) We then go on to study how chemical reaction rates are measured and calculated from molecular properties. Topics covered include: Energy, entropy, and the thermodynamic potentials; Chemical equilibrium; and Chemical kinetics.

Index of Topics:
0:00:06 Carnot Cycle
0:14:59 Efficiency
0:21:05 S is a State Function
0:26:43 Efficiency of Irreversible Processes
0:30:13 Clausius Inequality
0:33:42 The Second Law of Thermodynamics
Keywords: Chemistry